Viral and Bacterial Zoonotic Agents in Dromedary Camels from Southern Tunisia: A Seroprevalence Study - Simone Eckstein; Rosina Ehmann; Abderraouf Gritli; Mohamed Ben Rhaiem; Houcine Ben Yahia; Manuel Diehl; Roman Wölfel; Susann Handrick; Mohamed Ben Moussa; Kilian Stoecker (Microorganisms, 2022)
The rapid spread of SARS-CoV-2 clearly demonstrated the potential of zoonotic diseases to cause severe harm to public health. Having limited access to medical care combined with severe underreporting and a lack of active surveillance, Africa carries a high burden of neglected zoonotic diseases. Therefore, the epidemiological monitoring of pathogen circulation is essential. Recently, we found extensive Middle East respiratory syndrome coronavirus (MERS-CoV) prevalence in free-roaming dromedary camels from southern Tunisia. In this study, we aimed to investigate the seroprevalence, and thus the risk posed to public health, of two additional viral and two bacterial pathogens in Tunisian dromedaries: Rift Valley fever virus (RVFV), foot-and-mouth disease virus (FMDV), Coxiella burnetii and Brucella spp. via ELISA. With 73.6% seropositivity, most animals had previously been exposed to the causative agent of Q fever, C. burnetii. Additionally, 7.4% and 1.0% of the dromedaries had antibodies against Brucella and RVFV, respectively, while no evidence was found for the occurrence of FMDV. Our studies revealed considerable immunological evidence of various pathogens within Tunisian dromedary camels. Since these animals have intense contact with humans, they pose a high risk of transmitting serious zoonotic diseases during active infection. The identification of appropriate countermeasures is therefore highly desirable.